Detection of first- and second-line drug resistance in Mycobacterium tuberculosis clinical isolates by pyrosequencing - Engström, Anna (2012)
Conventional phenotypic drug susceptibility testing (DST) methods for Mycobacterium tuberculosis are laborious and very time-consuming. Early detection of drug-resistant tuberculosis (TB) is essential for prevention and control of TB transmission. We have developed a pyrosequencing method for simultaneous detection of mutations associated with resistance to rifampin, isoniazid, ethambutol, amikacin, kanamycin, capreomycin, and ofloxacin. Seven pyrosequencing assays were optimized for following loci: rpoB, katG, embB, rrs, gyrA, and the promoter regions of inhA and eis. The molecular method was evaluated on a panel of 290 clinical isolates of M. tuberculosis. In comparison to phenotypic DST, the pyrosequencing method demonstrated high specificity (100%) and sensitivity (94.6%) for detection of multidrug-resistant M. tuberculosis as well as high specificity (99.3%) and sensitivity (86.9%) for detection of extensively drug-resistant M. tuberculosis. The short turnaround time combined with multilocus sequencing of several isolates in parallel makes pyrosequencing an attractive method for drug resistance screening in M. tuberculosis.